The ritual of "Sharia al-Yad" throughout the history of Morocco Between the controls of custom and the developments of Islamic law - Youssef Mir (International Journal of Scientific Research and Innovative Studies, 2024)
Recently, many print and electronic media outlets have been reporting on practices that enshrine “street justice,” or what is known in Moroccan folklore as the ritual of “sharia of the hand,” through the agreement of the masses present to implement a customary punitive right against parties that have committed a forbidden act. These represent societal behaviors based on certain provocative actions, whether religious, cultural, social, or psychological. However, they remain unorganized behaviors that are not subject to institutional organization or are backed by certain parties with diverse religious orientations. Rather, they are merely individual or collective behaviors that are immediate and the result of a certain circumstance and are not based on judicial logic. Rather, they are the product of customs that draw their origins from Morocco’s ancient history. Keywords: Ritual, law of the hand, custom, law, legitimate violence, historical heritage, disciplinary punishment, dramatization of punishment, lawlessness. Received Date: February 25, 2024 Accepted Date: March 12, 2024 Published Date: April 17, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/206 DOI: https://doi.org/10.5281/zenodo.14148431